Modeliranje sestavov kovine in elastomerov z uporabo postopka končnih elementov - Floody, Sergio E. (Strojniški vestnik, 2007)
Metal-elastomer composite structures are an important tool for the reduction of mechanical vibrations. A structure that vibrates in flexure can be damped by the appropriate addition of a layer of damping material, for example, an elastomer, where the layer undergoes cyclic strain and thereby dissipates energy. However, the presence of the elastomer means that the structure is frequency dependent, which is a difficult case for obtaining accurate predictions since the solution of the corresponding eigenvalue problem is hardto compute. In this paper a methodology for modelling metal-elastomer composite structures using a finite-element approach is presented. In addition, a calculation scheme to approximate the solution of the frequency-dependent eigenvalue problem is discussed. The numerical results forthe inertness were compared with the experimental results for a classic composite sandwich beam. The method is extended to model and optimise Stockbridge absorbers used to suppress the aeolian vibrations of an actual electrical transmission line. Instead of tuning the absorber to some particular frequency, an objective function is defined and the physical dimensions of the absorber are optimised by means of a genetic algorithm. In this approach, the complete problem is analysed without using the modal strain-energy approach, implying that this modelling satisfies the causality principle. The method appears to be useful as a tool for designing and modelling metal-elastomer composite structures.
Keywords: kovine; elastomeri; kompoziti; modeliranje; vibracije; metoda končnih elementov; finite element method; dušilniki